Evolution of the energy band structure in chemical-bath-deposited CdS thin films studied by optical absorption spectroscopy - Asikoglu, A.; Yukselici, M. H. (IOP PUBLISHING LTD, 2011)
CdS thin films were grown on glass substrates by chemical bath deposition. Increasing deposition time from 10 to 200 min at an ultimate bath temperature of 60 degrees C gives rise to a red shift in optical absorption edge of similar to 1 eV and a decrease in the Urbach tail width from 520 to 370 meV. A semi-empirical model was developed to account for the decrease of band gap energy with deposition time based on possible lattice contraction at the earlier stages of thin film growth. The degree of structural disorder related to the Urbach tail width was shown to be proportional to unharmonic terms in potential energy of atoms vibrating asymmetrically. An increase in band gap energy with increasing heat-treatment temperature was observed and explained by a quantized-state effective mass model in the strong confinement limit which predicts a blue shift in band gap energy of similar to 0.5 eV as the grain size decreases from 7.6 to 2.2 nm due to a decrease in sulfur concentration in grains. Combined use of the Arrhenius plot and quantum size effect yields activation energy of 46 kJ mol(-1) for the diffusion of sulfur during the heat treatment.
Keywords: SOLAR-CELL; MECHANISM; GROWTH; CDTE; Engineering; Materials Science; Physics